2022
DOI: 10.3390/v14071373
|View full text |Cite
|
Sign up to set email alerts
|

HYGIEIA: HYpothesizing the Genesis of Infectious Diseases and Epidemics through an Integrated Systems Biology Approach

Abstract: More than two years on, the COVID-19 pandemic continues to wreak havoc around the world and has battle-tested the pandemic-situation responses of all major global governments. Two key areas of investigation that are still unclear are: the molecular mechanisms that lead to heterogenic patient outcomes, and the causes of Post COVID condition (AKA Long-COVID). In this paper, we introduce the HYGIEIA project, designed to respond to the enormous challenges of the COVID-19 pandemic through a multi-omic approach supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 140 publications
0
4
0
Order By: Relevance
“…Utilising such a protocol can significantly reduce the cost, time, and complexity required in performing exploratory proteomic studies on human plasma and is currently being applied in our setting to a large, 200 +, multi-timepoint patient cohort in a multi-omics context 29 . control; FDR, False discovery rate; HYGIEIA, Hypothesizing the genesis of infectious diseases and epidemics through an integrated systems biology approach; AUC, Area under the curve; PCA, Principal component analysis; PC, Principal component; QC, Quality control; SDS, Sodium dodecyl-sulfate; logFC, Log fold change; NLM, National library of medicine…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Utilising such a protocol can significantly reduce the cost, time, and complexity required in performing exploratory proteomic studies on human plasma and is currently being applied in our setting to a large, 200 +, multi-timepoint patient cohort in a multi-omics context 29 . control; FDR, False discovery rate; HYGIEIA, Hypothesizing the genesis of infectious diseases and epidemics through an integrated systems biology approach; AUC, Area under the curve; PCA, Principal component analysis; PC, Principal component; QC, Quality control; SDS, Sodium dodecyl-sulfate; logFC, Log fold change; NLM, National library of medicine…”
Section: Discussionmentioning
confidence: 99%
“…7 fractions are then concatenated into 3 pooled fractions, for a total MS run time of 360 minutes. Utilising such a protocol can significantly reduce the cost, time, and complexity required in performing exploratory proteomic studies on human plasma and is currently being applied in our setting to a large, 200 +, multi-timepoint patient cohort in a multi-omics context 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accelerated knowledge transfer on the brink of the current pandemic [ 58 ], which was largely decoupled from scientific peer review, has clearly shown that it is of extraordinary importance to structurally characterize discriminators (“statistically”) found in in silico datasets. This is independent of experimental data sources, such as relative copy numbers of specific mRNA polymers (genomics and expression patterns), the pattern differences in 2D protein gels or highly complex mass spectra attributable to the peptides of sample proteins (proteomics and peptidomics), or even the secondary metabolite patterns in biological samples (metabolomics).…”
Section: Molecule-centered Plant Biochemistry and Phytochemistrymentioning
confidence: 99%